Coking and gas products behavior of supercritical n-decane over NiO nanoparticle/nanosheets modified HZSM-5. (1st February 2020) - Long, Lin; Zhou, Weixing; Qiu, Yunfeng; Lan, Zhenzhong
Abstract: Endothermic hydrocarbon fuel of active thermal protection has great potential in cooling system. The bottlenecks for the practical application are the unsatisfied heat sink and severe coking issue. Here, NiO nanoparticle/nanosheet hybrid thin layers were successfully wrapped on the commercial HZSM-5 (denoted as ZSM-5@NiM ), and showing significant modulation ability for the acidity properties of HZSM-5 to boost supercritical cracking of n-decane. The as-prepared catalysts make the NiO and HZSM-5 show synergistic effect which dramatically lowers the overall acidity of composite, thus changes the cracking path of n-decane, and results in effective anti-coking properties. ZSM-5@NiM decelerated many additional free radicals and generated more gases products by monomolecular beta cleavage reaction. Gases products also show positively correlating with the heat sink. The catalysts improve the heat sink of n-decane from 3.77 MJ/kg at 728 °C to 4.59 MJ/kg at 780 °C. Present work demonstrates that the introduction of nanostructured metal oxides into HZSM-5 will synergistically adjust the acidity of composite, leading to the manipulation of catalytic cracking path and extent, gas products, heat sink, coking behavior of supercritical n-decane, finally providing deep insights for the design and fabrication of catalysts for hydrocarbon fuel cracking. Graphical abstract: Image 1 Highlights: NiO nanoparticle/nanosheets Modified HZSM-5 is facilely prepared. Acid amount of composites decreased and Lewis/Brönsted acid ratio increased. The ratio of cracking gas products increased with high ethylene and propylene. Coking is restrained due to the decreased total acid amount. Heat sink of supercritical n-decane is improved to 4.59 MJ/kg at 780 °C.